Substance P Stimulates Cyclooxygenase-2 and Prostaglandin E(2) Expression through JAK-STAT Activation in Human Colonic Epithelial Cells - Koon, Hon-Wai (2006)
Substance P (SP) via its neurokinin-1 receptor (NK-1R) regulates several gastrointestinal functions. We previously reported that NK-1R-mediated chloride secretion in the colon involves formation of PG. PGE(2) biosynthesis is controlled by cyclooxygenase-1 (COX-1) and COX-2, whose induction involves the STATs. In this study, we examined whether SP stimulates PGE(2) production and COX-2 expression in human nontransformed NCM460 colonocytes stably transfected with the human NK-1R (NCM460-NK-1R cells) and identified the pathways involved in this response. SP exposure time and dose dependently induced an early (1-min) phosphorylation of JAK2, STAT3, and STAT5, followed by COX-2 expression and PGE(2) production by 2 h. Pharmacologic experiments showed that PGE(2) production is dependent on newly synthesized COX-2, but COX-1 protein. Inhibition of protein kinase Cθ (PKCθ), but not PKCε and PKCδ, significantly reduced SP-induced COX-2 up-regulation, and JAK2, STAT3, and STAT5 phosphorylation. Pharmacological blockade of JAK inhibited SP-induced JAK2, STAT3, and STAT5 phosphorylation; COX-2 expression; and PGE(2) production. Transient transfection with JAK2 short-interferring RNA reduced COX-2 promoter activity and JAK2 phosphorylation, while RNA interference of STAT isoforms showed that STAT5 predominantly mediates SP-induced COX-2 promoter activity. Site-directed mutation of STAT binding sites on the COX-2 promoter completely abolished COX-2 promoter activity. Lastly, COX-2 expression was elevated in colon of mice during experimental colitis, and this effect was normalized by administration of the NK-1R antagonist CJ-12,255. Our results demonstrate that SP stimulates COX-2 expression and PGE(2) production in human colonocytes via activation of the JAK2-STAT3/5 pathway.